The Analisis Dhabt pada Manuskrip Mushaf Al-Quran Milik Azwardi di Nagari Tuo Pariangan Sumatera Barat - Fadli, Muhammad; Salim, Fadli; Mukmin, Ali; Rivaldi Silaban, Hasnan; Putra, Bilfahmi (Al-Irfani: Journal of Al Qur'anic and Tafsir, 2025)
This study aims to analyze the characteristics of dhabt in the Qur'anic manuscript owned by Azwardi in Nagari Tuo Pariangan. The method used is a qualitative approach with a library research type, where the primary source is the Qur'anic manuscript owned by Azwardi, and secondary sources include books, journal articles, and other related literature. The findings of this study reveal that the application of dhabt in the Qur'anic manuscript owned by Azwardi largely adheres to the rules established by dhabt scholars, particularly in aspects such as harakat, sukun/tanwin, and Tasydid. However, in the scope of hamzah, the Qur'anic manuscript owned by Azwardi does not yet fully comply with the rules set by dhabt scholars.